2023
DOI: 10.1186/s41182-023-00504-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, biology, pathogenesis, clinical manifestations, and diagnosis of dengue virus infection, and its trend in Ethiopia: a comprehensive literature review

Abstract: Dengue fever is a dengue virus infection, emerging rapidly and posing public health threat worldwide, primarily in tropical and subtropical countries. Nearly half of the world's population is now at risk of contracting the dengue virus, including new countries with no previous history-like Ethiopia. However, little is known about the epidemiology and impact of the disease in different countries. This is especially true in countries, where cases have recently begun to be reported. This review aims to summarize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 122 publications
1
20
0
Order By: Relevance
“…In this study, we examined factors associated with ART adherence in Selected Public Hospital of Addis Ababa. According to Ethiopian Demographic Heath Survey(EDHS) the overall education status in Addis Ababa where only36% of adults have received secondary education ( 20).Many researches indicated that there's an association between education and adherence level ( 21--22 ).In contrast , some studies reported that there's no association between adherence and educational status (23)(24).Our findings are consistent with the report of EDHS 2016.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, we examined factors associated with ART adherence in Selected Public Hospital of Addis Ababa. According to Ethiopian Demographic Heath Survey(EDHS) the overall education status in Addis Ababa where only36% of adults have received secondary education ( 20).Many researches indicated that there's an association between education and adherence level ( 21--22 ).In contrast , some studies reported that there's no association between adherence and educational status (23)(24).Our findings are consistent with the report of EDHS 2016.…”
Section: Discussionsupporting
confidence: 86%
“…The decision to transfuse platelets in dengue cases follows clinical criteria according to the treating physician but does not follow an evidence-based guideline [27,28]. Although there is still no protocol for managing and transfusion platelet agents, vaccination has been recognized as an essential pillar, in addition to vector control (repellents, mosquito nets, wastewater treatment), in the global approach to reducing the burden of dengue.…”
Section: Discussionmentioning
confidence: 99%
“…The four different dengue virus serotypes (DENV 1–4) are all spread by Aedes mosquitoes, primarily Aedes aegypti and to a lesser extent, Aedes albopictus [ 1 , 2 ]. All serotypes are known to produce the whole spectrum of dengue fever (DF) illnesses and share similar geographic patterns and host/vector interactions [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dengue fever is endemic in many countries across the World Health Organization (WHO) regions of Africa, the Americas, the Eastern Mediterranean, Asia, Australia, and the Western Pacific [ 4 , 5 ]. While the Americas, South-East Asia, and the Western Pacific are the most severely affected, Asia accounts for 70% of the global DF disease burden (10).…”
Section: Introductionmentioning
confidence: 99%